1994
DOI: 10.1111/j.1365-2621.1994.tb14710.x
|View full text |Cite
|
Sign up to set email alerts
|

Gingerol Decreases after Processing and Storage of Ginger

Abstract: Fresh cooked ginger and processed ginger products were extracted with methanol and analyzed by HPLC to study changes in the levels of [6]-,[8]-, and [lo]-gingerols after the products had been cooked and processed, and during storage of the products. Sensory tests evaluated the intensity of pungency in different processed products. Cooking and processing of paste-and-senbei decreased (p 2 0.05) ginger01 levels, but blanching and freeze-drvine: had no effect. Gingerols in all uroducts degraded gyadually with Gor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 11 publications
7
22
0
Order By: Relevance
“…The fresh ginger rhizomes investigated in this study contained 20.1 mg total pungent principles/g dry matter (dm) composed of 0.6, 14.1, 2.1 and 3.3 mg/g dm of 4-, 6-, 8-and 10-gingerol, respectively. The ratio of 6-, 8-, and 10-gingerols was 6.7:1:1.6, equal to that reported by Zhang, Iwaoka, Huang, Nakamoto, and Wong (1994), who investigated Hawaiian ginger rhizomes, but in contrast to Cho, Kim, Choi, Kim, and Hwang (2001), who determined a ratio of 11:1:1.2 for Brazilian ginger. In the fresh ginger rhizome, 12-gingerol as well as 6-shogaol was found in trace amounts, whereas 8-and 10-shogaol could not be detected.…”
Section: Quantification Of Pungent Principles During Ginger Digests Psupporting
confidence: 63%
See 2 more Smart Citations
“…The fresh ginger rhizomes investigated in this study contained 20.1 mg total pungent principles/g dry matter (dm) composed of 0.6, 14.1, 2.1 and 3.3 mg/g dm of 4-, 6-, 8-and 10-gingerol, respectively. The ratio of 6-, 8-, and 10-gingerols was 6.7:1:1.6, equal to that reported by Zhang, Iwaoka, Huang, Nakamoto, and Wong (1994), who investigated Hawaiian ginger rhizomes, but in contrast to Cho, Kim, Choi, Kim, and Hwang (2001), who determined a ratio of 11:1:1.2 for Brazilian ginger. In the fresh ginger rhizome, 12-gingerol as well as 6-shogaol was found in trace amounts, whereas 8-and 10-shogaol could not be detected.…”
Section: Quantification Of Pungent Principles During Ginger Digests Psupporting
confidence: 63%
“…This confirmed the freshness of the ginger rhizomes used, since dehydration of gingerols mainly occurred during heating and storage. Blanching the whole rhizomes at 90°C for 5 min, which did not destroy the parenchyma cell walls (Azian, Kamal, & Azlina, 2004), slightly diminished the total amounts of pungent principles protected by the cell matrix (Table 3), while in another study an increase of pungency after blanching at 120°C for 3 min has been observed (Zhang et al, 1994). Expectedly, fine grinding further reduced the pungency in the sample material due to cell decompartmentation, which releases the pungent principles from the protecting cell matrix into the surrounding tissue, and concomitantly due to frictional forces which arise during comminution.…”
Section: Quantification Of Pungent Principles During Ginger Digests Pmentioning
confidence: 95%
See 1 more Smart Citation
“…The gingerol content in UHT-treated samples stored at 4 and 25°C decreased by 8.30 and 8.46 %, respectively. Zhang et al (1994) have reported that gingerols in processed ginger products, such as fresh cooked ginger paste, blanched ginger, freeze-dried ginger, and ginger powder, decreased during storage. Gingerols can be transformed into shogaol homologues because of dehydration (Suekawa et al 1984).…”
Section: Gingerolsmentioning
confidence: 99%
“…The oily phenylpropanoid derivative gingerol has also been studied. Freeze-drying of ginger (Zingiber officinale) did not decrease the levels of the pungent principle, gingerol (Zhang et al, 1994).…”
Section: Effects On Other Constituentsmentioning
confidence: 99%